Additional notes on Orthalicidae from the Chimantá massif, Venezuelan Guayana, with descriptions of new species of Plekocheilus Guilding, 1828 (Mollusca: Gastropoda) - Breure, Abraham S. H.; Schlögl, Jan (Zootaxa, 2010)
Two new species are described from Venezuelan Guayana, Chimantá massif: Plekocheilus (P.) vlceki and P. (Eurytus) breweri. Some remarks are made on the ecology of the latter species in relation to birds. Finally some notes on conservation issues are made, highlighting possible threats by climate change.